James Brooke And Sarawak's Economic Growth - Wahyudhi, Johan (Institut Agama Islam Sumatera Barat Pariaman, 2023)
James Brooke was an important figure who made significant contributions to mining, agriculture and plantations in Sarawak. As Sarawak's first White Raja, he played a crucial role in developing these sectors and opening up new opportunities for economic growth in the region. This paper will expose James Brooke's efforts in advancing the economy in Sarawak based on primary and secondary sources found. The historical analysis that is emphasized is centered on explaining economic history covering the three areas mentioned earlier. The method of analysis used is the historical method by looking at the development of the three sectors within a certain period. Economic history itself is not a history that contradicts political history, but is an inseparable unity. In this region, political dominance is built on the development of local resources.